Effects of natural herbal extracts on hemp (Cannabis Sativa L.) oil quality indicators - Irfan Hamidioglu; Alvija Salaseviciene; Gintare Zaborskiene (Foods and Raw Materials, 2019)
The present research features such natural herbal extracts as rosemary (Rosmarinus officinalis L.), pome- granate (Punica granatum L.), and green tea (Camellia sinensis L.). Together with vitamin E, they were chosen to investigate hemp oil stability. The experiments revealed the effect of various fatty acids compositions on hemp oil properties. The effect of herbal extracts on the oxidative stability of oils was measured using the Rancimat method. The chemical tests included peroxide value (PV), free fatty acid (FFA) value, and acidity value (AV). Each herbal extract was applied in amounts of 30 mg/l and 50 mg/l. Vitamin E was mixed with the oil in the amount of 2 g/l. The changes in PV, FFA, AV, and fatty acid composition were measured on day 6, 12, 18, and 24. Hemp oil, pure or mixed with the extracts, was analyzed using the Rancimat method at 120°C with an airflow rate of 20 l/h to identify the in- duction periods (IP). IP values of oils with additional herbal extracts were found to be significantly higher (p < 0.05) than those of the control samples. The oil sample with vitamin E demonstrated the longest IP (4.12 hours at 120°C) during the Rancimat test. The herbal extracts and vitamin E had a positive effect on hemp oil PV compared with the control sample. Gas chromatography (GC) showed that hemp oil included a high amount of polyunsaturated Ome- ga-3 fatty acids, and the oil was not resistant to oxidation. In general, the natural herbal extracts and vitamin E in the recommended quantities had a positive effect on the oxidative stability of hemp oil.